Pengabdian Masyarakat Pembuatan Website Umkm Oleh-Oleh Tiga Putri - Abdillah, Muhammad Syarif; Wulan, Nur; Sitorus, Dicky Andreas; Ramadhan, Fahmi; Pratama, Wahyu; Fauzi, Ilham; Harahap, Renaldy (Unity Academy, 2025)
His study aims to develop a website for the MSME